Study on Anthropometric Characteristics Contributing to Success in Cricket: Investigating the relationship between anthropometric characteristics, physical fitness, and success in cricket (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The study is to camp are the Anthropometrics characteristics, body synthesis and physical fitness parameters of state level cricketers and national level cricketers. The essentialness was set as 0.05 level and classified’t’ esteem is 1.686. Anthropometrics characteristics was estimated by leading test which appears there is critical distinction in standing tallness (2.036>1.686), weight (2.024>1.686), leg length (2.058>1.686), a careful distance (2.026>1686), calf girths (2.024>1.686), upper arm sizes (2.045>1.686), thigh sizes (2.028>1.686). Body synthesis is estimated and it additionally shows critical contrast in triceps skin fold thickness (2.024>1.686). Biceps skinfold thickness (2.030>1.686), sub-scapula skin fold thickness (2.024>1.686). Physical fitness parameter speed, quality, nimbleness and adaptability was tried by directing 50 meter run (2.028>1.686), quality (2.032>1.686), spryness (2.026>1.686), adaptability (2.032>1.686) By leading study on 40 subjects i.e 20 state level cricketers and 20 national level cricketers it is seen that there is huge contrast in every one of the 14 variables. National level cricketers have better anthropometrics characteristics and physical fitness level than state level cricketers. Thus anthropometrics characteristics additionally upgrade performance level in cricket.